Drinking among Native American and White Youths: The Role of Perceived Neighborhood and School Environment - Friese, Bettina (J Ethn Subst Abuse, 2015)
This study examined whether differences in the perceived neighborhood and school environments account for differences in drinking behavior among Native American and White youths. Findings indicate that being Native American was indirectly related to drinking through perceived school and community variables. Higher drinking rates among Native Americans appear to be accounted for by lower school involvement, weaker neighborhood anti-drug norms, greater neighborhood disorganization and lower levels of perceived police enforcement. Results of this study highlight the potential importance of perceived school and neighborhood environments in drinking behavior among youths.